PERKEMBANGAN KOMODITI ASAL MALAYSIA YANG MASUK DI PASAR LOKAL KABUPATEN BENGKAYANG - B61112001, USTAMAN (Jurnal Ekonomi Daerah (JEDA), 2019)
USTAMANProgram Studi Magister Ilmu Ekonomi Fakultas Ekonomi dan Bisnis Universitas Tanjungpura                                 DOSEN PEMBIMBING 1                                  Dr.Afrizal, SE,M.Si                  Fakultas Ekonomi dan Bisnis Universitas Tanjungpura                              Dosen Pembimbing 2                               Helly Suharlina,SE, MM                Fakultas Ekonomi dan Bisnis Universitas Tanjungpura                                                 ABSTRAKCommodity Development is a process of change For The better. The success of The Investment (sales commodity) to on expected destination supplay Growth of Economic and succses improve poeples. Trade between Countries Border Area of Bengkayang Regency For Long Developing The Commodity Expand Malaysia Activity Trade The Years on Developing an Dommestic Product Bengkayang Regency Than Expand Border Area East Malaysia Sarikin. The Commodity Superior is Commodity of the Competition Product The Competitiveness on the local market Bengkayang Regency For Developing so market. Commodity Development Expand Malaysia in Bengkayang Regency. Trade Between Countries and The Improve Economic of The Bengkayang Regency Average 5,62%.Keywords : Commodity Development, Local Market.